Automated railway operations and control services - A. Ganga, Mrs.; Sruthi, G; Mahalakshmi, P; Sridhar, Amrutha (International Journal of Engineering and Technology, 2018)
The automatic railway system is a better replacement for the manual standard. The system directs to the controlling of railway gate, track switching, ticket buying and checking, train arrival recognizing and the security system enhancing in railway platform with cloud services. The entire system is automated; errors occurring due to manual operation can be prevented to minimize accidents occurring due to the indifferent and the negligent nature of the todayâ€™s world. The system employs two pair of IR sensors, one for the automatic gate control, and another for the track switching system. The IR sensors are the pivot in the detection of the arrival and departure of the train thus forming the Gate control system. The same mechanism used in the track switching unit to switch the track. The system that checks for proximity employs a KFS beacon, an on-off switch that forces the train to stop upon its presence and depart later. An electric vibrating motor is set in place to vibrate the platform upon trainâ€™s arrival and to alert the passenger who unknowingly steps over the specified limit. A rotating ultrasonic sensor embedded between the tracks, does the job of sensing a living being on the track near the platform and the gate controlling unit. Train Ticket payment and checker is initiated with Radio Frequency reader, GPS system and finger print scanning device with zero wait strategy. Therefore, the efficiently reliable system is operated automatically throughout the railway system.Â